2023
DOI: 10.1515/hc-2022-0157
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and antibacterial activity of a new poly azo compound containing N-arylsuccinimid and dibenzobarrelene moieties

Abstract: The present work describes the synthesis, characterization, and evaluation of the antibacterial activity of a new poly azo compound resulting from the coupling of a previously reported N-arylsuccinimid precursor 5 with the diazonium ion of aniline. This azo compound was characterized using its physical, elemental, and 1D and 2D spectroscopic data. The novel azo compound 7 (minimum inhibitory concentration [MIC] = 16–32 μg/mL) showed higher antibacterial activity than its precursor 5 (MIC = 32–64 μg/mL), althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Antibacterial studies of succinimide and sulphonyl moieties have also been reported. Some of the studies include 5-oxopyrrolidine derivatives against Staphylococcus aureus (Gram-positive bacterium directed activity), 30 pyrrolidine-2,5dione against Escherichia coli and Streptococcus pneumoniae, 31 N-aryl succinimide against S. aureus ATCC 25923 (Gram-positive bacterium) and K. pneumoniae 22, Salmonella 68R (Gramnegative bacterium), 32 N-sulfonamide 2-pyridones against Klebsiella pneumonia, Pseudomonas aeruginosa (Gram-negative bacterium) and Streptococcus mutans, Staphylococcus aureus (Gram-positive bacterium), 33 folic acid-sulfonamide conjugates against Gram-negative (P. aeruginosa and E. coli) and Grampositive (S. aureus and P. mirabilis) bacteria. 34 Based on the above reports and the biological importance of the succinimide moiety and sulphonyl scaffolds, significant interest has arisen in designing hybrid compounds of succinimide with sulphonyls to explore their biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial studies of succinimide and sulphonyl moieties have also been reported. Some of the studies include 5-oxopyrrolidine derivatives against Staphylococcus aureus (Gram-positive bacterium directed activity), 30 pyrrolidine-2,5dione against Escherichia coli and Streptococcus pneumoniae, 31 N-aryl succinimide against S. aureus ATCC 25923 (Gram-positive bacterium) and K. pneumoniae 22, Salmonella 68R (Gramnegative bacterium), 32 N-sulfonamide 2-pyridones against Klebsiella pneumonia, Pseudomonas aeruginosa (Gram-negative bacterium) and Streptococcus mutans, Staphylococcus aureus (Gram-positive bacterium), 33 folic acid-sulfonamide conjugates against Gram-negative (P. aeruginosa and E. coli) and Grampositive (S. aureus and P. mirabilis) bacteria. 34 Based on the above reports and the biological importance of the succinimide moiety and sulphonyl scaffolds, significant interest has arisen in designing hybrid compounds of succinimide with sulphonyls to explore their biological activities.…”
Section: Introductionmentioning
confidence: 99%